2019
DOI: 10.21203/rs.2.15199/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal Health and Access to Healthcare among Migrant Workers Engaged in Informal Construction Work, Ahmedabad, India

Abstract: Background:A large proportion of migrant women in India are employed in the urban informal economy, which is often characterized by low wages, precarious work conditions, poor living conditions and lack of social security. Circumstances such as these have deep implications for the health and overall wellbeing of workers. Our paper focuses on the intersection of migration, informal work and maternal health among female workers in the construction sector. We specifically seek to understand women’s perception and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This study observed that almost half of the women had made four ANC visits to the hospital or health center. This percentage is lower than the national average of 58% [13] as per NFHS-5 survey and lower than the Gujarat state average of almost 77% [6]. Thus, the ANC coverage was low, but it was still higher than that of the DLHS-3 survey of 2007-08, wherein ANC coverage was just 4%-14% among tribal women in Madhya Pradesh, Rajasthan, Odisha, and Chhattisgarh [14].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This study observed that almost half of the women had made four ANC visits to the hospital or health center. This percentage is lower than the national average of 58% [13] as per NFHS-5 survey and lower than the Gujarat state average of almost 77% [6]. Thus, the ANC coverage was low, but it was still higher than that of the DLHS-3 survey of 2007-08, wherein ANC coverage was just 4%-14% among tribal women in Madhya Pradesh, Rajasthan, Odisha, and Chhattisgarh [14].…”
Section: Discussionmentioning
confidence: 72%
“…The construction sector relies heavily on short-term migrant workers, offering dual work opportunities to both female and male workers. Female workers are often considered to be ‘helpers’ or ‘less skilled’ due to which they receive less than minimum wages, despite engaging of long hours of laborious and hazardous work [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ravindranath and Iannotti (2019) in their study based in Ahmedabad reveal that a considerable proportion of women workers (47%) suffered from low BMI. Participants reported that physical ailments, diseases and illnesses were a constant part of their lives.…”
Section: Health Vulnerabilities Associated With Female Migrantsmentioning
confidence: 97%